PEMODELAN RESERVOIR DALAM PENENTUAN DISTRIBUSI TEKANAN - , Wadeng
The mathematic al equation used in the reservoir modeling to determine pressure distribution is a diffusivity equation. The diffusivity equation is determinted by merging enegy conservation law, Darcys law and state equation in this non-linier equation. The diffusivity equation is solved numerical with the helped of Finite Element Method (FEM). The computer program simulation is generated using the Pascal language (7.0 Borland). Before using the program, the program has to be tested for test balance and injection by sinthetic reservoar modelling. The four cases of sinthetic reservoir model i.e production model, injection model, injection-production model and integrated aquifer-injection-production model, are interpreted. The result indicated that the program is valid. The pressure distribution is constant during balance test, and decreases modeling production test and increase modeling injection-aquifer test the layer as function of time. The interpretation indicates that thick phisical langer the porosity and permeability, then the smaller the well pressure as a function of time. The pressure distribution flactuates and finally constant at as steady-state is achieved at injection production model and at aquifer-injection-production model.